The Exaggerated Moral Claims of Evolutionary Psychologists - Pava, Moses L. (Journal of business ethics, 2008)
This article explores and examines some of the findings from the burgeoning field of evolutionary psychology. How important are these results to our understanding of morality and ethics? In addition, more specifically, how important are theses results to our understanding of business ethics? I believe that the jury is still out on these questions. This article: (1) summarizes some of the strengths of evolutionary psychology (of which there are several); (2) identifies specific findings and suggests that many of these findings are overstated and exaggerated; and (3) points out several methodological limitations and weaknesses. The article does not, in the end, recommend jettisoning evolutionary psychology. To the contrary, its point is that evolutionary psychology is a potentially useful method among many others to help us to better understand our “moral universe.” However, evolutionary psychology will never allow us to pierce through “the illusions that evolution and culture have saddled us with” as the psychologist Steven Pinker over-promises. This is true for the simple reason that science itself is both a product of evolution and a cultural practice. The aspiration of some evolutionary psychologists to transcend evolution (nature) and culture (nurture) through science is itself a dangerous illusion. Nevertheless, evolutionary psychology’s modest findings to date are a welcome contribution to anyone interested in making better and wiser ethical decisions, business or otherwise. The more knowledge we gain about our own brains and how they functions the better. These findings, however, should be subject to the same systematic scrutiny and healthy skepticism one would apply to any moral or ethical claim regardless of its origins. That is the purpose of this article.